Boosting the ORR performance of Fe-N/C catalyst via increasing the density and modifying the electronic structure of Fe-NX active sites. (20th January 2022) - Qu, Ximing; Li, Yanrong; Li, Guang; Ji, Ruiyi; Yin, Shuhu; Cheng, Xiaoyang; Wang, Chongtai; Yang, Jian; Jiang, Yanxia; Sun, Shigang
Highlights: Fe-N/C‑meso-evap with unique porous structure is prepared by doping sulfate. Fe-N/C‑meso-evap achieves high Fe-NX density by a second FeCl2 evaporation method. Fe-N/C‑meso-evap shows superior ORR activity with the E 1/2 of 0.835 v in acid media. Rich mesopores in Fe-N/C‑meso-evap increase the number of accessible active sites. Doped s facilitates the absorption of O2 and the breakage of OO bond. Abstract: Due to the existence of highly active Fe-NX coordination moieties, iron-nitrogen/carbon (Fe-N/C) materials have been considered as potential electrocatalysts toward oxygen reduction reaction (ORR). Increasing the density of Fe-NX sites is supposed to be a useful strategy to enhance the ORR performance of Fe-N/C catalysts. Herein, we report a stepwise synthesis strategy to construct Fe-N/C catalyst possessing a high ratio of mesopores and a high concentration of accessible Fe-NX active sites. Integrated with the properties of composition and morphology, the synthesized catalyst, Fe-N/C‑meso-evap, achieves remarkable ORR activity with a half potential of 0.835 V and a kinetic current density of 31.02 mA cm −2 at 0.8 V in 0.1 M HClO4 . This work provides new insight for designing single-atom catalysts towards ORR. Graphical abstract: Image, graphical abstract